Comparative review for theoretical and practical geospatial frameworks for effective building permitting lifecycle in municipalities - Aljobaly, O.; Abdulaal, W.; Maatouk, M. (Frontiers in Built Environment, 2025)
Municipal sector performance is significantly impacted by rapid urban sprawl globally, posing challenges for service providers in land management and the effective control of new building permitting processes. Technology has the potential to address these challenges; however, it does not resolve the lack of clarity in the municipality’s guidelines, which hinders the deployment of solutions. The study’s significance in improving the permitting process is considered a significant contributor to cities’ growth speed, quality, and growth directions. The study aims to examine building permit frameworks from a land management technology perspective to develop guidelines and frameworks that support effective building permitting processes. Integrating land management permitting processes and geospatial systems led to the adoption of technology that merges theoretical and practical frameworks, focusing on Geographic Information Systems (GIS) and Building Permitting Systems (BPS), as well as emerging technologies. The study was conducted by coding and pairing the main items among the theoretical and practical frameworks under the technology, process, organization, and legislation to define the areas of improving BPS. Hence, the research identified key components of selected frameworks between processes, technology, and organizations to identify guidelines for building a robust framework for future BPS considering geospatial data. Also, it emphasized standardizing data to enhance permit processing and land management efficiency and effectiveness.